Peningkatan Motif Dan Gaya Berjualan Daring Pada Masa Pandemi Covid 19 - Derivanti, Azizah Des (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2020)
Abstract - During the Distance Learning (DL) period, WhatsApp became the main communication medium between teachers and students, which is mediated by parents. This study aims to describe the interactions that occur between teachers and parents through social media. The study used the interaction theory, specifically the theory of interaction and interaction process analysis and group development. The method used is virtual ethnography. The study findings illustrate that interaction patterns between teachers, parents, and students for the teaching-learning process are slightly different when they are done through online media. Teachers are more likely to interact with parents in a two-way communication, where parents will then interact with students regarding the teachers’ messages. The interactions done are common, prominently in the form of task behaviors and socio-emotional behaviors. The emerged interactions involved six phases: evaluation, control, decision making, tension management, and integration. There’s a balanced interaction ratio between the task field and the socio-emotional field.